Nasal Reconstruction Using Tissue Expander and Modified Paramedian Forehead Flap Supported by Cartilage Graft - Pauline Yap; Nurul Syazana Mohamed Shah; Arman Zaharil Mat Saad; Wan Azman Wan Sulaiman; Siti Fatimah Noor Mat Johar (Istanbul University press, 2021)
This is an interesting case of a male patient with traumatic nasal injury with partial nasal amputation who was referred to our centre 3 months after the initial trauma. The wound was complicated with necrosis, the amputated nose had fallen off and a scar had formed at the wound bed. The nasal defect was greater than 2.5cm in length. More than 50% of the nose had fallen off including the bilateral alar lobule, the tip and the dorsal part of the nose. We utilized a tissue expander to create more tissue on the forehead in view of the patient’s short forehead, for donor site closure and to lengthen our flap. We performed a modified paramedian forehead flap with a widened distal portion of flap, in a two-staged nasal reconstruction surgery supported by L-strut cartilage graft harvested from the 7th rib. In this report we provide an illustrative description of the procedure, its cosmetic and functional outcome and we also share the challenges we faced.